2023
DOI: 10.1039/d3mh01313h
|View full text |Cite
|
Sign up to set email alerts
|

In situ dipole formation to achieve high open-circuit voltage in inverted perovskite solar cells via fluorinated pseudohalide engineering

Yuan Liu,
Chen Tang,
Anxin Sun
et al.

Abstract: EMIMTFSI can significantly lower the nonradiative recombination loss in p–i–n perovskite solar cells to achieve a champion power conversion efficiency of 24.81% with an impressive open-circuit voltage of 1.191 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Metal halide perovskite solar cells (PSCs) have emerged as a captivating focus of research within the realm of photovoltaics 1–11 and experienced a commendable advancement in photovoltaic conversion efficiency, soaring from an initial 3.8% to a remarkable 26.14%. 12 Moreover, commendable strides have been made in the fabrication of large-area PSCs, 13–15 bolstering their potential for promising commercialization and applications in diverse fields.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskite solar cells (PSCs) have emerged as a captivating focus of research within the realm of photovoltaics 1–11 and experienced a commendable advancement in photovoltaic conversion efficiency, soaring from an initial 3.8% to a remarkable 26.14%. 12 Moreover, commendable strides have been made in the fabrication of large-area PSCs, 13–15 bolstering their potential for promising commercialization and applications in diverse fields.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the directional dipole improves the local dielectric environment, thereby reducing the exciton binding energy and improve charge transport speed, greatly prolonging the carrier lifetime. Chen et al [134] doped the fluorinated pseudohalide ionic liquid (FPH-IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) into the perovskite phase. During the crystallization process of perovskite, EMIMTF-SI can accumulate and form an interface dipole layer at the top of the perovskite, significantly reducing exciton binding energy and nonradiative recombination, achieving a high V OC of 1.19 V for inverted devices.…”
Section: Perovskite Film Bulk Phasementioning
confidence: 99%
“…Moreover, the directional dipole improves the local dielectric environment, thereby reducing the exciton binding energy and improve charge transport speed, greatly prolonging the carrier lifetime. Chen et al [134] . doped the fluorinated pseudohalide ionic liquid (FPH‐IL) 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) into the perovskite phase.…”
Section: Dipole Effect In Pscsmentioning
confidence: 99%
“…The large dipole moment and stronger binding energy of 3‐TFPMAI may be beneficial to obtain the film with uniform morphology and improve carrier transport at the interface. [ 26,27 ] Experimental results indicated that the 3‐TFPMAI‐based 2D/3D perovskite film showed a smoother surface with fewer defects. In addition, 3‐TFPMAI modification can also adjust the energy level, thus accelerating the hole extraction and hole transporting.…”
Section: Introductionmentioning
confidence: 99%